Britain faces Europe - Pfaltzgraff, Robert L. (A Foreign Policy Research Institute book, 1969)
Britain Faces Europe is the first book to examine both the development of British policy and the evolution of attitudes in the British private sector toward European integration between 1957 and 1967.